PENGGUNAAN INFORMASI FINANSIAL DALAM MENGUKUR KINERJA ORGANISASI SEKTOR PUBLIK (STUDI PADA PUSKESMAS BAHU) - Tambariki, Brayel Topan; Karamoy, Herman; Tangkuman, Steven J. (Universitas Sam Ratulangi, 2018)
To succeed national development there are many aspects that must be considered. One of the most influential elements in national development is the budgetary. Budgetary issue is an important aspect, because it is one of the most vulnerable to fraud. Therefore, supervision of budget management should be held. In budgetary management, budget must fulfill three aspect of value for money, which are effectiveness, efficiency and economics. The State of Indonesia has many public sector organizations in various sectors. One of them is the organization in the health sector. Public sector organizations in the health sector are also important public sector organizations in national development, because they involve the interests of people's lives. In addition health is also one of the indicators in national development. Therefore, budget management in public sector organizations such as Puskesmas should be monitored for its performance, whether it is efficient, effective and economical. The purpose of this study is to determine the performance of Puskesmas Bahu based on the use of financial. This study used descriptive qualitative method. The results showed that financial information by measuring the level of economic, the level of efficiency and the level of effectiveness performance at the Puskesmas Bahu period 2014-2016 already fulfill the the aspect of value for money, whichÂ economical, efficient and effective.Keywords : Performance Measurement, Value For Money, Economic, Efficiency, Effectiveness